OpenGL superbible comprehensive tutorial and reference - Wright, Richard S. 1965- (Addison-Wesley, 2007)
OpenGL ® SuperBible, Fourth Edition, begins by illuminating the core techniques of "classic" OpenGL graphics programming, from drawing in space to geometric transformations, from lighting to texture mapping. The authors cover newer OpenGL capabilities, including OpenGL 2.1's powerful programmable pipeline, vertex and fragment shaders, and advanced buffers. They also present thorough, up-to-date introductions to OpenGL implementations on multiple platforms, including Windows, Mac OS X, GNU/Linux, UNIX, and embedded systems. Coverage includes · An entirely new chapter on OpenGL ES programming for handhelds · Completely rewritten chapters on OpenGL for Mac OS X and GNU/Linux · Up-to-the-minute coverage of OpenGL on Windows Vista · New material on floating-point color buffers and off-screen rendering · In-depth introductions to 3D modeling and object composition · Expert techniques for utilizing OpenGL's programmable shading language · Thorough coverage of curves, surfaces, interactive graphics, textures, shadows, and much more · A fully updated API reference, and an all-new section of full-color images You'll rely on this book constantly-whether you're learning OpenGL for the first time, deepening your graphics programming expertise, upgrading from older versions of OpenGL, or porting applications from other environments. Now part of the OpenGL Technical Library-The official knowledge resource for OpenGL developers The OpenGL Technical Library provides tutorial and reference books for OpenGL. The Library enables programmers to gain a practical understanding of OpenGL and shows them how to unlock its full potential. Originally developed by SGI, the Library continues to evolve under the auspices of the OpenGL Architecture Review Board (ARB) Steering Group (now part of the Khronos Group), an industry consortium responsible for guiding the evolution of OpenGL and related technologies. Contents Preface xxvii About the Authors xxxv Introduction 1 Part I: The Old Testament Chapter 1 Introduction to 3D Graphics and OpenGL 9 Chapter 2 Using OpenGL 33 Chapter 3 Drawing in Space: Geometric Primitives and Buffers 73 Chapter 4 Geometric Transformations: The Pipeline 127 Chapter 5 Color, Materials, and Lighting: The Basics 173 Chapter 6 More on Colors and Materials 229 Chapter 7 Imaging with OpenGL 251 Chapter 8 Texture Mapping: The Basics 303 Chapter 9 ...
Includes bibliographical references and index. - Print version record
Keywords: OpenGL; Computer graphics; Computer Graphics; Infographie; computer graphics; Computação gráfica